Accumulation of nutrients during the development of ‘Méndez’ avocado fruit - Salazar-García, Samuel; Álvarez-Bravo, Arturo; Ibarra-Estrada, Martha Elva; Mellado-Vázquez, Adriana (REVISTA TERRA LATINOAMERICANA, 2019)
Balanced and timely nutrition is important to ensure the yield and quality of avocado (Persea americana Mill.) fruit. This research was carried out in the cv. Méndez with the objectives of a) to describe the dynamics of fruit growth and the process of dry matter accumulation in mesocarp, b) to quantify the concentration and accumulation of nutrients in the mesocarp (pulp) during fruit development. In a commercial orchard with site-specif ic fertilization, 20 trees were selected and 30 summer flowering inflorescences per production cycle (2014-15, 2015-16 and 2016-17) were marked in each one. Five fruits per tree were randomly collected in f ive stages of development, from olive size to harvest, and the dry matter of the mesocarp and the concentrations of N, P, K, Ca, Mg, S, Fe, Cu, Mn, Zn and B in this tissue were quantif ied. The fruit required 300 days from anthesis to harvest. It showed accelerated growth in the f irst three stages of development (S-Olive, S-I and S-II) and lower growth in the last stage (S-III). Dry matter accumulation was constant during fruit development, although the largest accumulation occurred in S-III. In general, the concentration of nutrients in the mesocarp decreased with fruit development and its accumulation increased. The greatest fruit growth occurred in the f irst 185 post-anthesis days, when the mesocarp accumulated less than one-third of the total nutrients required until harvest. The results indicate the need to review how nutrients are supplied to the tree, to make sure they are adequately provided during fruit development.